The Right to Legal Assistance for Correctional Residents at the Class I State Detention Center, Central Jakarta - Hery Firmansyah; Diputra Syaban; Andrel Alshadad; Maria Magdalena Ina Reko; Siska Veronica Liu; Rieven Yehezkiel Nasari (JURNAL MAHASISWA YUSTISI, 2026)
As a state based on the rule of law, Indonesia guarantees equality before the law, including the right of underprivileged citizens to obtain legal aid and legal assistance. In practice, many inmates at the Class I State Detention Center of Central Jakarta still lack understanding of their rights as suspects or defendants, particularly regarding legal representation in criminal proceedings. This activity aimed to improve inmates’ understanding of the right to legal assistance, the stages of criminal justice proceedings, and the importance of access to legal aid as part of the principles of access to justice and fair trial. The program employed an empirical field-based approach through observation, interviews, legal counseling, interactive discussions, and direct legal consultation at Rutan Salemba. The activity was conducted offline and involved lecturers, students, and legal practitioners. The results showed that the inmates demonstrated strong enthusiasm and active participation during the counseling sessions, particularly in the question-and-answer and legal consultation sessions. Participants gained a better understanding of defendants’ rights, objection procedures to indictments, and access to free legal aid. In addition, several concrete legal cases were identified for further legal assistance. This activity concludes that legal counseling and legal assistance in detention centers play an important role in enhancing inmates’ legal awareness and supporting the fulfillment of their constitutional rights within the criminal justice process.